Food Resilience During Pandemic Covid-19 Based on Culture in Agriculture - Bahagia Bahagia; Leny Muniroh; Ritzkal Ritzkal; Abdul Karim Halim; Rimun Wibowo; M. Azhar Al-Wahid (LPPM Institut Nasional Laa Roiba Bogor, 2023)
The COVID-19 pandemic has an impact on human life in fulfilling food through agricultural activities. The purpose of this study is to find behaviors in the Sundanese culture perspective of the manager of the Sundanese cultural village in Bogor, West Java. The research method used is descriptive qualitative method. Meanwhile, the data collection method was carried out by three events, namely observation, documentation and in-depth interviews. While the data analysis using triangulation. The results of the study indicate that the construction of traditional food barns to store food is a step to achieve resilience because food needs are met. After that, food production follows the paranti line, namely agriculture that follows the way of ancestral rice farming and pest control is carried out organically so that it helps production but avoids food production failures in the future. Then the application of tritangtu in life so that the trust is always applied for progress. Keywords : Pandemic covid-19, culture, food, kampung budaya